2021
DOI: 10.1007/s40262-021-00984-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic, Pharmacodynamic, and Drug-Interaction Profile of Remdesivir, a SARS-CoV-2 Replication Inhibitor

Abstract: Remdesivir (RDV, Veklury ® ) is a once-daily, nucleoside ribonucleic acid polymerase inhibitor of severe acute respiratory syndrome coronavirus 2 replication. Remdesivir has been granted approvals in several countries for use in adults and children hospitalized with severe coronavirus disease 2019 (COVID-19). Inside the cell, remdesivir undergoes metabolic activation to form the intracellular active triphosphate metabolite, GS-443902 (detected in peripheral blood mononuclear cells), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 31 publications
7
107
0
Order By: Relevance
“…8.1, Certara, NJ, USA) software. Due to the impossibility to perform intensive PK sampling on critical patients, the estimation of elimination t1/2 for GS-441524 was based on two points (period between 15-24 h), assuming a constant t1/2 at this late elimination timings, as reported in previous works [13][14][15] .…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…8.1, Certara, NJ, USA) software. Due to the impossibility to perform intensive PK sampling on critical patients, the estimation of elimination t1/2 for GS-441524 was based on two points (period between 15-24 h), assuming a constant t1/2 at this late elimination timings, as reported in previous works [13][14][15] .…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…The method was validated following FDA and EMA guidelines, showing contained bias and coefficients of variation (all <15% for both RDV and GS-441524) and good linearity (linear R 2 >0.996) [13][14][15] .…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Additionally in combination with HCV partner A number of very recent researches are evidencing the importance of GS-441524 as a potent antiviral drug due to its strong binding properties with NSP3 macrodomain and NSP12-NSP8-NSP7 of SARS Cov 2 [34], [35] . It has also been proven that this molecule has very less retention value inside host body as most of the residue is eliminated with urine suspecting no side effect [36] . Amazingly out of the majority of Remdesivir in clinical trial experiments, recovered in urine was found to be in form of GS-441524; whereas only 10% recovered as remdesivir [37], [38] .…”
Section: Discussionmentioning
confidence: 99%
“…We develop a PK model to describe the distribution in the body of the remdesivir (RDV) prodrug and its active triphosphate metabolite GS-443902, (RDV-TP) parametrized using data from Humeniuk et al (2020) [15]. We focus on these two components because the metabolic pathway leading from extracellular RDV to intracellular RDV-TP is not yet confirmed [15][16][17]. However, there is consensus that intracellular RDV-TP is the active form of the drug [16][17][18].…”
Section: Pharmacokinetic Modelmentioning
confidence: 99%
“…The metabolic pathway leading from extracellular RDV to intracellular RDV-TP is not yet confirmed [15][16][17]. However, there is consensus that intracellular RDV-TP is the active form of the drug [16][17][18]. For the purpose of this study, we therefore a novel PK model to describe the distribution in the body of the remdesivir (RDV) prodrug and its active triphosphate metabolite GS-443902, (RDV-TP), parametrized using data from safety and tolerability investigations reported in Humeniuk et al (2020) [15].…”
Section: Introductionmentioning
confidence: 99%